Scaling up - From Vision to Large-Scale Change - A Management Framework for Practitioners - and Cooley, Larry; Kohl, Richard; Ved, Rajani R. (MSI, 2016)
This document was originally published in 2006 and re-issued in a substantially revised Second Edition in 2012.